The Urgency of Amending Article 251 of the KUHD Related to The Principle of the Utmost Good Faith in Insurance Agreements: (Critical Note on the Decision of the Constitutional Court Case Number 83/PUU-XXII/2024) - Agus Yudha Hernoko; Fitri Nur Amalia; Ridaningjati , Pamungkas; Kinan Kalam Khalifa; Antonino Pedro Marçal (Jurnal Suara Hukum, 2025)
This paper critically examines the Constitutional Court Decision Number 83/PUU-XXII/2024, which reviews the constitutionality of Article 251 of the Indonesian Commercial Code (KUHD) concerning the principle of utmost good faith in insurance contracts. The article stipulates that coverage becomes void if the insured conceals any facts, even if done in good faith. The urgency of this writing lies in the necessity to interpret Article 251 of the KUHD systematically and teleologically, particularly within the context of legal protection for both insurers and insured parties. This research employs a normative juridical approach with a prescriptive analysis of legal norms and the implications of the Court’s decision. The findings indicate that the phrase “renders the insurance void” in Article 251 of the KUHD should not be construed as void by law (nietig van rechtswege) but rather voidable (vernietigbaar), as it concerns the subjective element of mutual consent. The Court's decision has significant implications for restructuring insurance contract norms to ensure fair and proportional protection for all parties involved.